Early Carboniferous gabbro and basalt in the St. Peters area, southern Cape Breton Island, Nova Scotia - Barr, S.; Grammatikopoulos, A.; Dunning, G. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1994)
Small gabbroic plutons and minor mafic volcanic rocks occur in the St Peters area of southwestern Cape Breton Island. U-Pb dating of zircon and baddeleyite show that the gabbro has an Early Carboniferous age of 339 ± 2 Ma, similar to the age of the surrounding sedimentary units of the Horton and Windsor groups. The gabbros were intruded at shallow depth, consis tent with their association with minor mafic volcanic rocks. Penological studies suggest that evolution of the gabbros in volved fractionation of Mg-rich olivine and pyroxene, but not significant plagioclase. The chemical characteristics of the suite have been partly modified by alteration, evidenced in albitization of plagioclase and zones of carbonate alteration, but generally indicate a continental within-plato tectonic setting and tholciitic affinity. The parent magma may have been de pleted in heavy rare-earth elements, and was possibly derived from a garnet-bearing mantle source. The St Peters gabbros and basalts are part of widespread mid-Devonian to Carboniferous igneous activity in Atlantic Canada, apparently related to extension during the development of the Maritimes Basin.